Retinal ganglion cell topography and spatial resolution in the Japanese smelt Hypomesus nipponensis (McAllister, 1963) - Pushchin, Igor (J Anat, 2020)
Vision plays a crucial role in the life of the vast majority of vertebrate species. The spatial arrangement of retinal ganglion cells has been reported to be related to a species’ visual behavior. There are many studies focusing on the ganglion cell topography in bony fish species. However, there are still large gaps in our knowledge on the subject. We studied the topography of retinal ganglion cells (GCs) in the Japanese smelt Hypomesus nipponensis, a highly visual teleostean fish with a complex life cycle. DAPI labeling was used to visualize cell nuclei in the ganglion cell and inner plexiform layers. The ganglion cell layer was relatively thin (about 6‐8 μm), even in areas of increased cell density (area retinae temporalis), and was normally composed of a single layer of cells. In all retinal regions, rare cells occurred in the inner plexiform layer. Nissl‐stained retinae were used to estimate the proportion of displaced amacrine cells and glia in different retinal regions. In all retinal regions, about 84.5% of cells in the GC layer were found to be ganglion cells. The density of GCs varied across the retina in a regular way. It was minimum (3990 and 2380 cells/mm(2) in the smaller and larger fish, respectively) in the dorsal and ventral periphery. It gradually increased centripetally and reached a maximum of 14,275 and 10,960 cells/mm(2) (in the smaller and larger fish, respectively) in the temporal retina, where a pronounced area retinae temporalis was detected. The total number of GCs varied from 177 × 10(3) (smaller fish) to 212 × 10(3) cells (larger fish). The theoretical anatomical spatial resolution (the anatomical estimate of the upper limit of visual acuity calculated from the density of GCs and eye geometry and expressed in cycles per degree) was minimum in the ventral periphery (smaller fish, 1.46 cpd; larger fish, 1.26 cpd) and maximum in area retinae temporalis (smaller fish, 2.83 cpd; larger fish, 2.75 cpd). The relatively high density of GCs and the presence of area retinae temporalis in the Japanese smelt are consistent with its highly visual behavior. The present findings contribute to our understanding of the factors affecting the topography of retinal ganglion cells and visual acuity in fish.